A novel pathogenic variant in OSBPL2 linked to hereditary late-onset deafness in a Mongolian family - Ningjin Wu; Husile Husile; Liqing Yang; Yaning Cao; Xing Li; Wenyan Huo; Haihua Bai; Yangjian Liu; Qizhu Wu (BMC, 2019)
Abstract Background To investigate the clinical features and the underlying causal gene of a family with hereditary late-onset deafness in Inner Mongolia of China, and to provide evidence for the early genetic screening and diagnosis of this disease. Methods Family data were collected to draw a pedigree. Audiological testing and physical examination of the family members were conducted following questionnaire. Genomic DNA was extracted from peripheral blood of 5 family members (3 patients and 2 normal control) and subjected to whole genome sequencing for identifying deafness casual genes. The pathogenic variant in the deafness gene was further confirmed by Sanger sequencing. Results The family is composed of a total of 6 generations, with 53 traceable individuals. In this family,19 of them were diagnosed with post lingual deafness with the age of onset between 10 and 40 years, displaying delayed and progressive hearing loss. Patients with hearing loss showed bilateral symmetry and mild to severe sensorineural deafness. The pattern of deafness inheritance in this family is autosomal dominant. Whole genome sequencing identified a novel pathogenic frameshift mutation, c.158_159delAA (p.Gln53Arg fs*100) in the gene OSBPL2 (Oxysterol-binding protein-related protein 2, NM_144498.2), which is absent from genomic data of 201 unrelated normal subjects. This pathogenic variant was further validated by Sanger sequencing, and was found to co-segregate in this family. Conclusions Whole genome sequencing identified a two-nucleotide deletion in OSBPL2 (c.158_159delAA) as the pathogenic variant for deafness in the family. Our finding expands the mutational spectrum of OSBPL2 and contributes to the pathogenic variant list in genetic counseling for deafness screening.